Modelling and simulation of an absorption solar cooling system for Cyprus - Florides, Georgios A.; Kalogirou, Soteris A.; Tassou, Savvas A.; Wrobel, L. C. (My University, 2002)
In this paper a modelling and simulation of an absorption solar cooling system is presented. The system is modelled with the TRNSYS simulation program and the typical meteorological year file containing the weather parameters of Nicosia, Cyprus. Initially a system optimisation is carried out in order to select the appropriate type of collector, the optimum size of storage tank, the optimum collector slope and area, and the optimum thermostat setting of the auxiliary boiler. The final optimised system consists of a 15-m2 compound parabolic collector tilted 30° from the horizontal and a 600-l hot water storage tank. The collector area is determined by performing the life cycle analysis of the system. The optimum solar system selected gives life cycle savings of C£1376 when a nonsubsidized fuel cost is considered. The system operates with maximum performance when the auxiliary boiler thermostat is set at 87°C. The system long-term integrated performance shows that 84,240 MJ required for cooling and 41,263 MJ for hot water production are supplied with solar energy.
Keywords: Cooling system; TRNSYS simulation program